The magnitude of untreated dental caries and its predictors among pregnant women attending antenatal care at health facilities in Gondar town, Northwest Ethiopia - Amare Teshome Tefera; Solomon Berhe; Samuel Seifu; Martha Solomon; Zelalem Ayichew; Aynishet Adane; Wubet Birhan; Tadesse Awoke Ayele; Shashe Zewdu (BMC Pregnancy and Childbirth)
Abstract Introduction Pregnancy-associated hormonal alterations and reduced immunological function contribute to diminished oral hygiene, thereby increasing the susceptibility of pregnant women to oral diseases, especially dental caries. Despite the high burden of dental caries among pregnant women, there is a lack of evidence on the magnitude of untreated dental caries and its predictors in Ethiopia. Hence, this study aimed to assess the magnitude of untreated dental caries and its associated factors among pregnant women attending antenatal care at Gondar town health facilities. Methods A facility-based cross-sectional study was conducted among pregnant women attending antenatal care at Gondar town health facilities from February 2024 to June 2024. Data were collected by health professionals using pretested structured interviewer-administered questionnaires and intraoral examinations. The collected data was exported to Stata version 17 for data analysis. A binary logistic regression analysis was done to identify risk indicators of dental caries among pregnant women. Hosmer’s and Lemeshow’s goodness of fit test was used to check the fitness of the model. Results Of the total 628 pregnant women who participated in this study, 312 (49.7, 95%CI: 45.7,53.7) were found to have untreated dental caries. Age (AOR = 1.06, 95%CI: 1.01,1.11), primary educational attainment (AOR = 0.47, 95%CI: 0.24, 0.94), college-level education or beyond (AOR = 0.51, 95%CI: 0.26, 0.99), no regular tooth brushing habit (AOR = 1.41, 95%CI: 1.01, 1.99) and parity (AOR = 1.20, 95%CI: 1.01,1.44) were predictors of untreated dental caries among pregnant women. Conclusion The study demonstrated a high level of untreated dental caries experience among pregnant women. Age, educational status, parity, and toothbrushing practice significantly affect dental caries development among pregnant women. Midwives and ANC providers should be trained in basic oral health training procedures. Pregnant women with multiple pregnancies and irregular tooth brushing practices should practice frequent teeth brushing to decrease the burden of untreated dental caries. Ministry of Health should integrate oral health education into their ANC program and promote dental referrals for high-risk pregnancies to decrease the burden of untreated dental caries.